Animation of Thwaites Glacier ice base and surface elevation profiles from June 2011 to November 2020 - Bevan, Suzanne; Luckman, Adrian; Benn, Douglas (NERC EDS UK Polar Data Centre, 2021)
Thwaites Glacier, West Antarctica. An animated time series plot of 64 profiles of ice base and surface elevation along a flowline based on the mean flow direction. The flowline passes through a region of large elevation change that took place between 2014 and 2017. The work was funded by NERC projects NE/P011365/1 and NE/S006605/1 : The profiles were extracted from digital elevation models (DEMs) based on an interferometric analysis of TanDEM-X satellite system synthetic aperture radar (SAR) data. Phase-scaling of the interferograms utilised the supplied orbit data. The DEMs were geocoded first using the RAMP DEM (Liu et al., 2015) and then, iteratively, using the DEMs themselves. The DEMs were calibrated in the vertical using an ICESat-2 point at (107.49°W, 75.47°S) acquired on 2018-11-05. Heights are plotted relative to the EGM2008 Geoid and corrected for mean dynamic topography and tides. The ice base is computed assuming that the ice is in hydrostatic equilibrium. The bedrock is from Jordan et al. (2020). Processing is described fully in the reference paper. : Interferometric analysis was carried out using Gamma Remote Sensing software 20190603. : Via comparison with ICESat-2 data and in consideration of orbit uncertainty, the original DEMs have an estimated vertical uncertainty of ±2 m.